Comparison of the impacts of cytostatic compounds of maleimide derivative and 5-fluorouracil on the morphofunctional status of rat’s liver under conditions of colon carcinogenesis - Danylov, M. O.; Ostrovska, G.V.; Rybalchenko, V.K. (Reports of the National Academy of Sciences of Ukraine, 2014)
The maleimide derivative 1-(4-Cl-benzyl)-3-Cl-4-(CF3-phenylamino)-1H-pyrrol-2,5-dione causes no destructive effect on the histological structure in rat's liver after the 7 week administation. It also has a partial protective effect under the conditions of colon carcinogenesis, induced by 1,2-dimethylhydrazine, unlike traditional anticancer drug 5-fluorouracil, which showed hepatotoxic effects.